Aktivitas Jamaah Tabligh dalam Proses Edukasi Masyarakat di Kota Makasar - Abdul Rahman (Kasta: Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2023)
This study aims to determine the activities of the Tablighi Jamaat at Headquarters and in the community, the influence of the Tablighi Jamaat's activities; and to find out how the community responds to the existence of the Tablighi Jamaat. The research used in this study is a qualitative research presented descriptively (descriptive research), namely research procedures that produce descriptive data in the form of written or spoken words and activities from the behavior of people who are observed using observation, interviews and documentation methods. The results of this study indicate that: (1) Tablighi Jamaat activities are carried out at the headquarters, at the Tablighi Jamaat headquarters carrying out routine activities, namely every Tuesday night and Friday night. On Tuesday night the main activity is to submit reports for each halaqoh, while on Friday night the main activities are parrots and khuruj activities. Meanwhile, there are three activities in the community, namely, Khuruj, Jaulah, and Ta'lim. (2) the influence of the activities of the Tablighi Jamaat is very large, namely it can change the attitudes and behavior of the community and especially on individuals. (3) The public's responses were pro and some were against the Tablighi Jamaat